Kinetic Regularity of the Formation of Fe(II)–Fe(III) LDH Structures (Green Rust) on the Steel Surface in Presence of the FeSO4 and Fe2(SO4)3 Water Solutions - Lavrynenko, O.M.; Korol, Ya.D.; Netreba, S.V.; Prokopenko, V.A. (Хімія, фізика та технологія поверхні, 2010)
The kinetic regularity of origin and transformation of the Fe (II)–Fe (III) LDH structures on the steel electrodes surface contacting with FeSO4 and Fe2(SO4)3 dispersion medium at free access of the air oxygen into the system was studied. X-ray diffraction was chosen as the main method of investigation. It was shown that regardless of oxidation level of iron with its concentration 102–103 mg/dm3 on electrode surface the GR(SO4 2-) phase was formed staying single for almost 5 hours. The phase transformation of embryonic GR(SO4 2-) surface structures occur with formation of morphological composites of iron-oxygen g -row: lepidocrocite g -FeOOH and magnetite Fe3O4, and α-row structure representative, goethite α-FeOOH.